New lower jaw and teeth referred to Maxakalisaurus topai (Titanosauria: Aeolosaurini) and their implications for the phylogeny of titanosaurid sauropods - Marco A.G. França; Júlio C. de A. Marsola; Douglas Riff; Annie S. Hsiou; Max C. Langer (PeerJ, 2016)
Sauropod dinosaurs compose a diversified, well known, and worldwide distributed clade, with a stereotyped body plan: deep trunk, elongated neck and tail, columnar limbs and very small skull. In Brazil, the group is represented by ten formally described Cretaceous species, mostly titanosaurs. This is the case of Maxakalisaurus topai, known based on an incomplete and disarticulated skeleton, unearthed from deposits of the Adamantina Formation in Minas Gerais. Here, we report a partial right dentary, including five isolated teeth, collected from the same site as the type-series of M. topai and tentatively referred to that taxon. The bone is gently curved medially, the functional teeth are set on an anterolingual position, and two replacement teeth are seen per alveoli. New morphological data gathered from that specimen was employed to conduct a comprehensive phylogenetic analysis of Titanosauria (with 42 taxa and 253 characters), based on previous studies. The Aeolosaurini clade was recovered, with Gondwanatitan and Aelosaurus as sister taxa, and Maxakalisaurus, Panamericansaurus, and Rinconsaurus forming a basal polytomy.